Learning with cases - Mauffette-Leenders, Louise A. (Richard Ivey School of Business, University of Western Ontario, 2007)
This book is about learning by the case method. Written from a student perspective, it focuses on learning fast and effectively. It provides in-depth coverage of the three-stage learning process: (1) individual preparation; (2) small group discussion; and (3) large group discussion. It also gives useful aids through the Case Difficulty Cube, the Short and Long Cycle Processes of individual preparation, the Case Preparation Chart, and suggestions for small and large group effectiveness as well as case presentations, reports, and exams. This text focuses on a professional and ethical approach to learning, invaluable for those who wish to distinguish themselves in their future careers.